Porous current collector and preparation method and application thereof
By using porous skeleton structure of porous current collector and lithium-philic fluoride in lithium metal batteries, the problems of lithium dendrites growth and volume expansion are solved, the performance and safety of the battery are improved, and the production cost is reduced.
Patent Information
- Application Number
- CN202411701977.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The prior art is difficult to effectively inhibit the growth of lithium dendrites and the volume expansion of negative electrodes in lithium metal batteries, resulting in reduced battery performance and safety risks.
Using a porous current collector, including a conductive substrate, a porous polymer and a lithium-philic fluoride MFx, a three-dimensional porous hybrid conductive structure is formed by constructing a porous framework structure and dispersing a lithium-philic fluoride, which inhibits the growth of lithium dendrites and the formation of dead lithium.
Effectively alleviate the growth of lithium dendrites, inhibit the expansion of lithium metal negative electrodes, improve the cycle life and safety of the battery, and reduce production costs and facilitate large-scale production.
Smart Images

Figure CN119297295A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium metal batteries and relates to a porous current collector and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have attracted great interest as power storage systems for electric vehicles and smart grids. To break through the limits of lithium-ion batteries, lithium metal anodes (with an ultra-high theoretical specific capacity of 3860 mAh g -1 ) matched with high capacity / high voltage positive electrode is the research direction of the next generation of high energy batteries.
[0003] However, highly reactive lithium metal anodes are often prone to cause a large number of side reactions, forming unstable solid electrolyte interface films, leading to lithium dendrite growth and even volume expansion and dead lithium generation, which affects battery performance and brings serious safety hazards, thus limiting their commercialization.
[0004] Suppressing the growth and volume expansion of lithium dendrites is an urgent problem to be solved in lithium metal batteries. Researchers have suppressed the growth of lithium dendrites by constructing artificial solid electrolyte interface membranes. For example, CN113690485A discloses a solid electrolyte interface membrane, an alkali metal electrode and a preparation method thereof, wherein the solid electrolyte interface membrane comprises a polymer layer formed by the reaction of polyoxometalates and 1,3-dioxolane. A flexible, self-healing polymer layer is generated by the polymerization of polyacid anions in polyoxometalates with cations of 1,3-dioxolane to suppress the growth of alkali metal dendrites. The realization of the entire preparation process is similar to the response to biological information stimulation, and is a method for preparing a self-healing artificial solid electrolyte interface membrane that simulates the response of gene editing technology. At the same time, due to its flexible characteristics, the risk of SEI membranes with poor mechanical properties breaking with long-term cycling of alkali metal batteries is reduced, thereby avoiding the safety problems caused by the growth of alkali metal dendrites, which is beneficial to improving the electrochemical performance of the battery. CN110512306A discloses a method for preparing an electrolyte membrane for inhibiting the growth of lithium dendrites in a solid-state lithium battery, the method comprising the following steps: using polyacrylonitrile PAN, polymethyl methacrylate PMMA, and linear polymer to prepare spinning solutions for coaxial spinning, heat-treating the formed membrane material during the spinning process and then rapidly cooling and solidifying it after stretching, wherein the flow rates of each solution during the solution spinning process are PMMA>linear polymer>PAN; then the membrane material is placed in a lithium-ion battery electrolyte for immersion; finally, the membrane material is placed at 80-90°C for treatment for 14.5-15.5 minutes to obtain the desired solid electrolyte membrane, wherein the solid electrolyte membrane is a multilayer core-shell structure fiber composite film of PMMA / linear polymer / PAN. This patent can effectively solve the shortcomings of PMMA's poor mechanical properties that make it difficult to inhibit the growth of lithium dendrites and PAN's instability to lithium metal.
[0005] However, the method of inhibiting the growth of lithium dendrites by constructing an artificial solid electrolyte interface film is often prone to more serious side reactions and interface instability. Dendrite growth can also be alleviated by regulating liquid electrolytes or designing solid electrolytes. CN116979157A discloses a preparation method and application of an aqueous composite electrolyte for inhibiting zinc dendrite growth, comprising the following steps: S1), taking a certain amount of aqueous soluble zinc salt and a sugar additive and mixing them evenly; S2), adding deionized water, fixing the volume, and stirring continuously until dissolved, and standing until the pH value of the composite aqueous electrolyte is stable to obtain a stable aqueous composite electrolyte containing a sugar organic additive that inhibits dendrite growth. However, regulating the composition of the electrolyte may also cause the interface impedance to become larger, and the volume expansion cannot be effectively inhibited.
[0006] Therefore, providing an improved strategy for the current collector so that it can effectively suppress the dendrite problem in lithium metal batteries and effectively reduce the volume expansion of the negative electrode is a technical problem that needs to be solved urgently. Summary of the invention
[0007] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a porous current collector and a preparation method and application thereof.
[0008] To achieve the above object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a porous current collector, the porous current collector comprising a conductive substrate, a porous polymer disposed on the conductive substrate, and a lithium-philic fluoride MF dispersed on the surface of the porous polymer. x , wherein M is an element that can form an alloy with Li, and x satisfies the valence balance.
[0010] The present invention forms a three-dimensional porous current collector with a porous mixed conductive structure by constructing a porous polymer on a conductive substrate and dispersing a lithium-philic fluoride on its surface. The current collector can be used in lithium metal batteries to effectively alleviate the growth of lithium dendrites, inhibit the expansion of lithium metal negative electrodes, and avoid the generation of dead lithium. The technical principle is as follows:
[0011] First, the porous structure allows lithium to be deposited preferentially inside the current collector, achieving dense lithium metal deposition, reducing negative electrode volume expansion and avoiding surface dendrite growth and dead lithium formation. Second, lithium-philic fluoride (MF x ) can react with lithium metal to form LiM alloy and LiF. LiF has good Li + Conductivity, LiM alloy has high mechanical strength, which helps to construct a stable SEI film and inhibit the growth of lithium dendrites.
[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0013] Preferably, the conductive substrate is selected from at least one of a carbon material film layer having a porous structure or a metal substrate, and is preferably a carbon material film layer having a porous structure.
[0014] In the present invention, by adopting a carbon material film layer with a porous structure and forming a porous polymer and a lithium-philic fluoride on its surface, the battery can obtain better performance. This is because: a conductive network with a porous skeleton structure is formed in the current collector, which is beneficial to the transmission and diffusion of lithium ions, effectively reducing the local current density on the surface, thereby alleviating the growth of lithium dendrites, and is beneficial to the high-rate charging and discharging of the battery.
[0015] Preferably, the carbon material film layer with a porous structure includes at least one of carbon fabric, carbon nanotube film, carbon paper and graphene film. Among them, the carbon nanotube film is a porous skeleton structure composed of one-dimensional carbon nanotubes overlapped with each other. The graphene film is a porous skeleton structure composed of two-dimensional graphene overlapped with each other.
[0016] Preferably, the metal substrate comprises at least one of copper foil, copper mesh and carbon-coated copper foil.
[0017] Preferably, the thickness of the conductive substrate is 40μm-100μm, for example, it can be 40μm, 42μm, 44μm, 45μm, 47μm, 48μm, 50μm, 52μm, 55μm, 56μm, 58μm, 60μm, 65μm, 67μm, 70μm, 80μm, 90μm or 100μm, etc.
[0018] Preferably, the thickness of the porous polymer is 5μm-30μm, for example, it can be 5μm, 6μm, 8μm, 9μm, 10μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 20μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm or 30μm, etc.
[0019] Preferably, the lithiophilic fluoride MF x The thickness is 3μm-10μm, for example, it can be 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm or 10μm, etc.
[0020] As a preferred technical solution of the porous current collector of the present invention, the porous polymer is prepared by non-solvent induced phase separation technology.
[0021] Preferably, the polymer in the porous polymer includes at least one of polyvinyl alcohol, polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polypropylene oxide, polymethyl methacrylate and polyvinylidene chloride.
[0022] Preferably, the MF x M in the formula is selected from at least one of Mg, Al, In, Si, Ag, Bi, Fe, Co, Cu and Ni, preferably at least one of Mg, Al and In. x Specifically, it can be MgF2, AlF3, InF3, SiF4, AgF, BiF3, FeF3, CoF3, CuF2, NiF2, etc.
[0023] In a second aspect, the present invention provides a method for preparing the porous current collector as described in the first aspect, the preparation method comprising the following steps:
[0024] (1) dissolving a polymer in a first solvent to obtain a polymer solution, coating the polymer solution on a substrate, and then immersing the substrate in a second solvent to exchange the first solvent with the second solvent;
[0025] (2) After the exchange is completed, spray MF on the polymer surface x , and a porous current collector is obtained after drying.
[0026] The method of the present invention can simply and quickly construct a porous polymer layer through non-solvent induced phase separation technology, which helps to alleviate the growth of lithium dendrites and the formation of dead lithium. Lithiaphilic fluoride helps to construct a more stable SEI film, thereby effectively improving the cycle life and safety of lithium metal batteries. Moreover, the non-solvent induced phase separation method for manufacturing porous current collectors is simple and controllable, does not require the addition of additional pore-forming agents, reduces costs, and is easy to mass produce.
[0027] Preferably, the polymer is soluble in the first solvent but insoluble in the second solvent, and the first solvent and the second solvent are miscible with each other.
[0028] Preferably, in step (1), the mass concentration of the polymer solution is 5wt%-20wt%, for example, it can be 5wt%, 7wt%, 8wt%, 9wt%, 10wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%, etc.
[0029] Preferably, the conductive substrate is selected from at least one of a carbon material film layer having a porous structure or a metal substrate, and is preferably a carbon material film layer having a porous structure.
[0030] In the method of the present invention, when the substrate is a carbon material film layer with a porous structure, the porous polymer layer and the porous carbon material film layer will interact with each other, and a part of the porous polymer will be filled into the local pores of the carbon material film layer, thereby constructing a porous mixed conductive structure for the current collector, which helps to alleviate the growth of lithium dendrites and the formation of dead lithium. Lithophilic fluoride helps to construct a more stable SEI film, thereby effectively improving the cycle life and safety of lithium metal batteries.
[0031] Preferably, the carbon material film layer having a porous structure includes at least one of carbon fabric, carbon nanotube film, carbon paper and graphene film.
[0032] Preferably, the metal substrate comprises at least one of copper foil, copper mesh and carbon-coated copper foil.
[0033] Preferably, in step (1), the coating is immediately immersed in the second solvent after the coating.
[0034] Preferably, in step (1), after immersing in the second solvent, the mixture is allowed to stand for 5 h to 8 h, for example, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h or 8 h.
[0035] As a preferred technical solution of the method for preparing the porous current collector of the present invention, in the spraying step of step (2), MF x The spraying is carried out in the form of a solution, and the mass concentration of the solution is 3wt%-10wt%, for example, it can be 3wt%, 4wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt% or 10wt%, etc.
[0036] Preferably, the drying in step (2) is vacuum drying.
[0037] Preferably, the drying temperature in step (2) is 80°C-90°C, for example, it can be 80°C, 82°C, 83°C, 84°C, 85°C, 86°C, 88°C or 90°C; the drying time is 4h-5h, for example, it can be 4h, 4.2h, 4.3h, 4.4h, 4.5h, 4.6h, 4.7h, 4.8h, 4.9h or 5h.
[0038] In a third aspect, the present invention provides a negative electrode, comprising the porous current collector described in the first aspect and lithium deposited on the porous current collector.
[0039] In a fourth aspect, the present invention provides a lithium metal negative electrode, wherein the lithium metal battery comprises the negative electrode described in the third aspect.
[0040] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] (1) The present invention forms a three-dimensional porous current collector with a porous mixed conductive structure by constructing a porous polymer on a conductive substrate and dispersing a lithium-philic fluoride on its surface. The current collector can be used in lithium metal batteries to effectively alleviate the growth of lithium dendrites, inhibit the expansion of lithium metal negative electrodes, and avoid the generation of dead lithium.
[0043] (2) In the present invention, by adopting a carbon material film layer with a porous structure and forming a porous polymer and a lithium-philic fluoride on its surface, the battery can obtain better performance. This is because: a conductive network with a porous skeleton structure is formed in the current collector, which is beneficial to the transmission and diffusion of lithium ions, effectively reducing the local current density on the surface, thereby alleviating the growth of lithium dendrites, and at the same time facilitating high-rate charging and discharging of the battery.
[0044] (3) The non-solvent-induced phase separation method for manufacturing porous current collectors is simple and controllable, does not require the addition of additional pore-forming agents, reduces costs, and facilitates large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a schematic diagram of the structure of the porous current collector of Example 1, wherein: 1. a conductive substrate; 2. a porous polymer; and 3. a lithium-philic fluoride. DETAILED DESCRIPTION
[0046] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0047] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0048] Example 1
[0049] This embodiment provides a porous current collector, and its structural schematic diagram is shown in Figure 1 , comprising a conductive substrate 1 (50 μm thick), a porous polymer 2 (20 μm thick) disposed on the conductive substrate 1, and a lithiophilic fluoride 3 (5 μm thick) dispersed on the surface of the porous polymer 2, wherein the conductive substrate 1 is a carbon nanotube film, the polymer in the porous polymer 2 is polyvinyl alcohol, and the lithiophilic fluoride 3 is MgF2.
[0050] This embodiment also provides a method for preparing the above-mentioned porous current collector, comprising the following steps:
[0051] Polyvinyl alcohol (PVA) was added to a certain amount of water, and stirred at 80°C for 5 hours to prepare a polymer solution with a concentration of 10wt%. The evenly stirred polymer solution was scraped on a carbon nanotube film (CF) with a thickness of 50μm, and then immediately immersed in a propanol solution and allowed to stand for 6 hours. After the solvent and the non-solvent were fully exchanged, a layer of porous polymer was formed on the carbon nanotube film. Then, a 5wt% MgF2 dimethyl sulfoxide solution was sprayed on the current collector, and finally the current collector was placed in an 80°C oven for vacuum drying for 5 hours to completely remove the residual solvent, thereby obtaining a porous current collector, referred to as MgF2 / PVA / CF porous current collector.
[0052] Example 2
[0053] This embodiment provides a porous current collector, including a conductive substrate (thickness 50 μm), a porous polymer (thickness 25 μm) arranged on the conductive substrate, and a lithium-philic fluoride (thickness 3 μm) dispersed on the surface of the porous polymer, wherein the conductive substrate is a carbon nanotube film, the polymer in the porous polymer is polyethylene oxide, and the lithium-philic fluoride is AlF3.
[0054] This embodiment also provides a method for preparing the above-mentioned porous current collector, comprising the following steps:
[0055] Polyethylene oxide (PEO) is added to a certain amount of water and stirred at 60°C for 5 hours to prepare a polymer solution with a concentration of 8wt%. The evenly stirred polymer solution is scraped on a carbon nanotube film (CF) with a thickness of 50μm, and then immediately immersed in an ethylene glycol solution and allowed to stand for 6 hours. After the solvent and the non-solvent are fully exchanged, a layer of porous polymer will be formed on the carbon nanotube film. Then, a 3wt% AlF3 dimethyl sulfoxide solution is sprayed on the current collector, and finally the current collector is placed in an 80°C oven for vacuum drying for 5 hours to completely remove the residual solvent, thereby obtaining a porous current collector, referred to as AlF3 / PEO / CF porous current collector.
[0056] Example 3
[0057] This embodiment provides a porous current collector, including a conductive substrate (50 μm thick), a porous polymer (10 μm thick) disposed on the conductive substrate, and a lithium-philic fluoride (8 μm thick) dispersed on the surface of the porous polymer, wherein the conductive substrate is carbon paper, the polymer in the porous polymer is polyvinylidene fluoride, and the lithium-philic fluoride is InF3.
[0058] This embodiment also provides a method for preparing the above-mentioned porous current collector, comprising the following steps:
[0059] Polyvinylidene fluoride (PVDF) is added to a certain amount of N,N-dimethylformamide, and stirred at 60°C for 5 hours to prepare a polymer solution with a concentration of 15wt%. The evenly stirred polymer solution is scraped on a carbon paper (CP) with a thickness of 50μm, and then immediately immersed in an aqueous solution and allowed to stand for 6 hours. After the solvent and the non-solvent are fully exchanged, a layer of porous polymer will be formed on the carbon paper. Then, an 8wt% InF3 dimethyl sulfoxide solution is sprayed on the current collector, and finally the current collector is placed in an 80°C oven for vacuum drying for 5 hours to completely remove the residual solvent, thereby obtaining a porous current collector, referred to as InF3 / PVDF / CP porous current collector.
[0060] Example 4
[0061] This embodiment provides a porous current collector, and the preparation method thereof is different from that of Embodiment 1 in that the carbon nanotube film is replaced with a copper foil of equal thickness (50 μm).
[0062] Example 5
[0063] This embodiment provides a porous current collector, and its preparation method is different from that of Embodiment 1 in that MgF2 is replaced by NiF2.
[0064] Example 6
[0065] This embodiment provides a porous current collector, and the preparation method thereof is different from that of Embodiment 1 in that the concentration of the polymer solution is adjusted to 3 wt %.
[0066] Example 7
[0067] This embodiment provides a porous current collector, and the preparation method thereof is different from that of Embodiment 1 in that the concentration of the polymer solution is adjusted to 22 wt %.
[0068] Example 8
[0069] This embodiment provides a porous current collector, and the preparation method thereof is different from that of Embodiment 1 in that the standing time is 4 hours.
[0070] Example 9
[0071] This embodiment provides a porous current collector, and the preparation method thereof is different from that of Embodiment 1 in that the standing time is 9 hours.
[0072] Comparative Example 1
[0073] This comparative example provides a current collector. The difference between the preparation method and that of Example 1 is that the following operation of "immediately immersing in a propanol solution and standing for 6 hours" is omitted.
[0074] Comparative Example 2
[0075] This comparative example provides a current collector, and the preparation method is different from that of Example 2 in that the lithiophilic fluoride is replaced by aluminum oxide.
[0076] Application Example 1
[0077] A lithium metal negative electrode is provided, and the preparation method thereof is as follows:
[0078] The porous current collector prepared in Example 1 was assembled into a battery with a lithium sheet. The separator used was a 9 μm polyethylene film. The electrolyte used was a 1 mol / L LiTFSI solution of 1,3-dioxolane / ethylene glycol dimethyl ether (DOL / DME volume ratio was 1:1, and the solution contained 1.0 wt% LiNO3 additive). The battery was charged at 2 mA cm -1 The battery was discharged at a constant current density of 3 h to deposit lithium on the porous current collector to obtain the negative electrode, which is referred to as Li-MgF2 / PVA / CF electrode.
[0079] Application Example 2-9
[0080] A lithium metal negative electrode is provided. The difference between its preparation method and that of Application Example 1 is that the porous current collectors prepared in Examples 2-9 are respectively used to assemble a battery with a lithium sheet, and the rest of the contents are the same as those of Application Example 1.
[0081] Comparative Application Example 1-2
[0082] A lithium metal negative electrode is provided. The difference between its preparation method and that of Application Example 1 is that a porous current collector prepared in Comparative Example 1-2 is used to assemble a battery with a lithium sheet, and the rest of the contents are the same as those of Application Example 1.
[0083] Making and testing lithium metal batteries:
[0084] (I) Production of lithium metal batteries:
[0085] The positive electrode material NCM811 (chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2), carbon black Super P and PVDF are mixed evenly in a mass ratio of 98:1:1, NMP is added to make a positive electrode slurry, coated on aluminum foil and dried to obtain a positive electrode sheet, which is assembled into a battery with the lithium metal negative electrode of Application Examples 1-9 and Comparative Application Example 1. The separator used is a 9μm polyethylene film, and the electrolyte used is a 1.0moL / L LiTFSI 1,3-dioxolane / ethylene glycol dimethyl ether solution (DOL / DME volume ratio is 1:1, and the solution contains 1.0wt% LiNO3 additive).
[0086] (II) Cycle test of lithium metal batteries:
[0087] The assembled lithium metal battery was charged to 3.4V at 0.01C constant current, 3.8V at 0.05C constant current, 4.2V at 0.1C constant current and constant voltage, and then discharged to 2.8V at 0.2C constant current for 3 cycles to form a complete SEI film. Then, the battery was charged to 4.2V at 0.3C constant current and constant voltage, and discharged to 2.8V at 1C constant current for cyclic testing, and the first efficiency, capacity retention rate and coulombic efficiency were recorded. The test results are shown in Table 1.
[0088] Table 1
[0089] First effect / % Number of cycles Capacity retention rate / % Coulomb efficiency / % Application Example 1 89.90 200 98.5 99.92 Application Example 2 89.69 200 97.2 99.94 Application Example 3 90.17 200 98.0 99.94 Application Example 4 88.77 200 90.2 99.32 Application Example 5 88.02 200 86.1 99.07 Application Example 6 86.78 100 80.0 94.28 Application Example 7 84.50 100 73.7 93.97 Application Example 8 88.39 200 75.5 98.81 Application Example 9 89.19 200 77.3 98.40 Comparative application example 1 82.49 100 65.9 92.67 Comparative Application Example 2 87.20 100 78.9 98.11
[0090] It can be seen from Table 1 that the porous current collector of the present invention is applied to lithium metal batteries, which can effectively improve the electrochemical performance of the battery, especially the cycle performance is greatly improved. This is because the porous current collector of the present invention can effectively alleviate the growth of lithium dendrites, inhibit the expansion of the lithium metal negative electrode, and avoid the generation of dead lithium.
[0091] By comparing Application Example 1 with Application Example 4, it can be seen that compared with the two-dimensional planar current collector (copper foil), the three-dimensional porous current collector (carbon nanotube film) can induce lithium metal to deposit inside the current collector, alleviate surface dendrite growth, and thus improve the cycle performance of lithium metal batteries.
[0092] By comparing Application Example 1 with Application Example 5, it can be seen that MgF2 has better lithium affinity than NiF2, which helps to construct a more stable SEI film and inhibit the growth of lithium dendrites.
[0093] By comparing Application Example 1 with Application Examples 6-7, it can be seen that if the concentration of the polymer solution is too low, it is not conducive to forming a uniform porous polymer layer; if the concentration of the polymer solution is too high, it will affect the electronic conductivity of the current collector, which is not conducive to the battery cycle.
[0094] By comparing Application Example 1 with Application Examples 8-9, it can be seen that if the exchange time with the second solvent is too short, it is not conducive to the formation of pores; if the exchange time is too long, it is not conducive to the formation of uniform pores, thus deteriorating the performance of the current collector in the battery.
[0095] By comparing Application Example 1 with Comparative Application Example 1, it can be seen that if the polymer is not exchanged with the second solvent, a porous polymer cannot be formed, and only a polymer layer is formed on the surface of the current collector, which is not conducive to lithium ion conduction, thereby deteriorating battery performance.
[0096] By comparing Application Example 1 with Comparative Application Example 2, it can be seen that aluminum oxide has no lithium affinity and cannot form an alloy layer and a LiF-rich SEI layer on the negative electrode surface in a lithium metal battery, and has no effect on improving battery performance.
[0097] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A porous current collector, characterized in that: The porous current collector includes a conductive substrate, a porous polymer disposed on the conductive substrate, and a lithium-philic fluoride MF dispersed on the surface of the porous polymer. x , wherein M is an element that can form an alloy with Li, and x satisfies the valence balance.
2. The porous current collector according to claim 1, characterized in that: The conductive substrate is selected from at least one of a carbon material film layer having a porous structure or a metal substrate, and is preferably a carbon material film layer having a porous structure; Preferably, the carbon material film layer having a porous structure comprises at least one of carbon fabric, carbon nanotube film, carbon paper and graphene film; Preferably, the metal substrate comprises at least one of copper foil, copper mesh and carbon-coated copper foil.
3. The porous current collector according to claim 1 or 2, characterized in that: The thickness of the conductive substrate is 40 μm-100 μm; Preferably, the thickness of the porous polymer is 5 μm-30 μm; Preferably, the lithiophilic fluoride MF x The thickness is 3μm-10μm.
4. The porous current collector according to any one of claims 1 to 3, characterized in that: The porous polymer is prepared by non-solvent induced phase separation technology; Preferably, the polymer in the porous polymer includes at least one of polyvinyl alcohol, polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polypropylene oxide, polymethyl methacrylate and polyvinylidene chloride.
5. The porous current collector according to any one of claims 1 to 4, characterized in that: The MF x The M in it is selected from at least one of Mg, Al, In, Si, Ag, Bi, Fe, Co, Cu and Ni, and is preferably at least one of Mg, Al and In.
6. A method for preparing a porous current collector according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) dissolving a polymer in a first solvent to obtain a polymer solution, coating the polymer solution on a conductive substrate, and then immersing the conductive substrate in a second solvent to exchange the first solvent with the second solvent; (2) After the exchange is completed, spray MF on the polymer surface x , and a porous current collector is obtained after drying.
7. The preparation method according to claim 6, characterized in that: In step (1), the polymer is soluble in a first solvent but insoluble in a second solvent, and the first solvent and the second solvent are miscible with each other; Preferably, in step (1), the mass concentration of the polymer solution is 5wt%-20wt%; Preferably, the conductive substrate is selected from at least one of a carbon material film layer having a porous structure or a metal substrate, and is preferably a carbon material film layer having a porous structure; Preferably, the carbon material film layer having a porous structure comprises at least one of carbon fabric, carbon nanotube film, carbon paper and graphene film; Preferably, the metal substrate comprises at least one of copper foil, copper mesh and carbon-coated copper foil; Preferably, in step (1), the coating is immediately immersed in the second solvent after the coating; Preferably, in step (1), the mixture is immersed in the second solvent and then allowed to stand for 5 h to 8 h.
8. The preparation method according to claim 6 or 7, characterized in that: In the spraying step of step (2), MF x Spraying is carried out in the form of a solution, the mass concentration of the solution is 3wt%-10wt%; Preferably, the drying in step (2) is vacuum drying; Preferably, the drying temperature in step (2) is 80° C.-90° C., and the drying time is 4 h-5 h.
9. A negative electrode, characterized in that The negative electrode comprises the porous current collector according to any one of claims 1 to 5 and lithium deposited on the porous current collector.
10. A lithium metal battery, characterized in that: The lithium metal battery comprises the negative electrode according to claim 9.
Citation Information
Patent Citations
Three-dimensional porous metal lithium negative electrode for secondary battery and preparation and application thereof
CN111799443A
Porous carbon current collector and electrochemical device
CN114026717A
Lithium metal composite pole piece as well as preparation method and application thereof
CN115911263A
Modification method and application of negative current collector of lithium metal battery
CN116230951A
Negative electrode material for lithium ion battery and lithium ion battery
CN117477069A